Meta-analysis/Shmeta-analysis - Shapiro, Samuel (Oxford University Press, 1994)
Editor‘s note: This and the following two commentaries (pages 779 and 783) are based on presentations made at the symposium “Meta-analysis of Observational Studies” at the 26th Annual Meeting of the Society for Epidemiologic Research, Keystone, Colorado, June 16—18, 1993. Dr. Shapiro‘s response to Drs. Petitti and Greenland follows on page 788.